Internet Of Things-Proactive Security Approach - Thiab, Ali Shawket; Shibghatullah, Abdul Samad; Mohd Yusoh, Zeratul Izzah (Medwell Journals, 2018)
The proposed solution in this study is to use a proactive WPA/WPA2 approach in order to secure the access link side of the IoT. The proactive approach is controlled by a DDWRT router which changes the password proactively after a specific time interval after instructing the connected devices to do so as well. The solution uses an IPsec security on the end routers to ensure the data security on the public internet side of the connection. This simple solution allows using a simple Wi-Fi setup or even better to use the current Wi-Fi infrastructure which is available in almost every enterprise or home environment where the IoT is needed. A separate Wi-Fi network will be created for the IoT devices, so that, the current normal users experience will not change. The solution proved to be secure by evaluating the three security pillars: confidentiality, integrity and availability.